Recent Advances in Dimeric Cycloparaphenylenes as Nanotube Fragments - Li, Ke; Sun, Zhe (Synlett, 2021)
Since the discovery of cycloparaphenylenes in 2008, the chemical synthesis of more-complicated molecular systems with curved π-surfaces has been vigorously sought, giving rise to a plethora of new exciting molecules with various topologies and functions. This Synpacts article briefly summarizes recent examples of carbon nanohoop dimers, highlighting three examples as nanotube fragments. Their synthesis, isomerization, photophysical properties, and host–guest chemistry are discussed.1 Introduction2 Synthetic Strategy toward Nanotube Dimers3 Isomerization Dynamics of Nanotube Dimers4 Photophysical Properties of Nanotube Dimers5 Host–Guest Chemistry of Nanotube Dimers6 Conclusions
Keywords: carbon nanohoops; nanotube dimers; isomerization; host–guest chemistry